Analysis of the Implementation of Students' Religious Character Education Through Islamic Habituation in Elementary Schools: Analisis Pelaksanaan Pendidikan Karakter Religius Siswa Melalui Pembiasaan Islami di Sekolah Dasar - Febriyanti, Lindania; Amrullah, Muhlasin (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine the implementation of religious character education for students at SD Muhammadiyah 9 Ngaban, and how to overcome obstacles in implementing Islamic habits in SD Muhammadiyah 9 Ngaban. The research method used is descriptive qualitative research. The research subjects were the principal, third grade teachers and third grade students. By using data collection techniques of observation, interviews and documentation. The results of this study indicate that Islamic habituation is carried out consistently and on a scheduled basis. The implementation of religious character education at SD Muhammadiyah 9 Ngaban is integrated into self-development programs, learning activities and character values ​​developed by the school. The obstacles encountered did not dampen the enthusiasm of teachers to continue implementing activities related to Islamic habituation. Keywords – Implementation of Character Education, Religion, Islamic Habituation